Protracted COVID-19 during Treatment of Facial Palsy - Mehrdad Hasibi; Maral Seyed Ahadi; Hamed Abdollahi; Mehrdad Jafari (Case Reports in Neurological Medicine)
Neurologic manifestations are increasingly reported as the coronavirus disease 2019 (COVID-19) pandemic continues. This is a report of a COVID-19 patient with Bell's palsy. Case Summary. A 52-year-old man with fever and malaise was tested positive for COVID-19. After a week, he developed right-sided peripheral facial palsy and was treated with corticosteroids in conjunction with antiviral treatment which resulted in complete recovery. Discussion. Concomitant treatment of corticosteroids and antiviral treatment can decrease morbidity in patients with COVID-19-related Bell's palsy.